Photocatalyst-free photochemical deuteration via H/D exchange with D2O - Ying Meng; Bei Shu; Jing Zhang; Heng Rao; Ziyuan Zhou; Zhiyuan Wang; Zhongyi Liu; Kangdong Liu; Yueteng Zhang; Wei Wang (Nature Communications)
Abstract Deuterium labeling is increasingly important across scientific fields, from drug development to materials engineering, but current methods often require expensive catalysts. Here we demonstrate a simple, photocatalyst-free approach for incorporating deuterium into organic molecules using visible light. By employing common thiol compounds under mild blue-light irradiation (380–420 nm), we successfully modify two key chemical groups (formyl and α-amino) with high efficiency (up to 96% deuterium incorporation). This method eliminates the need for specialized PCs, significantly reducing costs and complexity. Surprisingly, we find that the system generates reactive intermediates (thiyl radicals and hydrogen atoms) through previously unrecognized light-activated pathways. These discoveries challenge conventional assumptions about photochemical deuteration and offer practical advantages for both laboratory research and industrial-scale production. Our results provide a more sustainable and scalable route to deuterated compounds while opening possibilities for light-driven chemistry without expensive catalysts. This work advances isotope labeling technology and suggests broader applications for simple, light-powered reactions in chemical synthesis.